Drop Impact of Gelatin Coating Formulated with Cellulose Nanofibers on Banana and Eggplant Epicarps - Osorio-Lira, F; Andrade-Pizarro, R (Academic Press, 2015)
Drop impact on a solid surface has received attention for a variety of industrial applications, such as in edible coatings by spray methods. In the present work, drop impact behavior of edible coating formulations (ECF) based on gelatin, glycerol and cellulose nanofibers on banana and eggplant epicarps was studied. Drops of ECF were generated by a precision flat tipped syringe needle connected to a digitally controlled syringe pump. A high-speed camera recorded the spreading dynamics of impacting drops and the maximum spread diameter was determined by ImageJ program. Maximum spread factor is dependent upon the concentration of gelatin and cellulose nanofibers since these components modify the viscosity and surface tension, respectively. For coating formulations with low viscosity, ξmax∝We0.24±0.01, while for formulations with high viscosity, ξmax∝We0.19±0.02. © 2014 Elsevier Ltd.